Microimplant assisted rapid palatal expansion vs surgically assisted rapid palatal expansion for maxillary transverse discrepancy treatment - Oliveira, Cibele Braga de [UNESP]; Ayub, Priscila [UNESP]; Ledra, Ingrid Muller [UNESP]; Murata, Wilson Humio; Suzuki, Selly Sayuri; Ravelli, Dirceu Barnabe [UNESP]; Santos-Pinto, Ary [UNESP] (Elsevier B.V., 2021)
Introduction: This study compared the skeletal and dental changes of microimplant assisted rapid palatal expansion (MARPE) with those produced by surgically assisted rapid maxillary expansion (SARPE) in postpeak adolescents and adults. Methods: The sample comprised 17 patients (mean age, 26 +/- 11 years) selected for the MARPE group and 15 (mean age, 28.5 +/- 10.5 years) selected for the SARPE group. Cone-beam computed tomography scans taken just before and after the expansion were used to assess dental and skeletal changes and compare the changes between the groups. Results: MARPE showed greater transversal skeletal changes in the midface and posterior and anterior maxillary base measurements. The transverse displacement of the alveolar process was greater but not significant for the SARPE group than the MARPE group. Regarding dental effects, the root distance measurements did not differ between the groups, but SARPE produced a significantly greater increase in intermolar and interpremolar distance and a greater buccal inclination of the alveolar process and supporting teeth than MARPE. Conclusions: The MARPE technique showed an increase in skeletal transverse maxillary expansion at the midface and basal bone compared with SARPE, especially at the posterior palatal region; however, no difference was found in the expansion of the alveolar process between the 2 methods. MARPE presented a more parallel expansion in both a coronal and axial view, whereas SARPE led to a V-shaped opening. The greater buccal inclination of the alveolar process and supporting teeth was observed in the SARPE group. (Am J Orthod Dentofacial Orthop 2021;159:733-42)